Pharmacological therapy of metabolic dysfunction-associated steatotic liver disease-driven hepatocellular carcinoma - Wang, Yumin; Fleishman, Joshua S.; Li, Tongda; Li, Yulin; Ren, Zhao; Chen, Jichao; Ding, Mingchao (Frontiers in Pharmacology, 2024)
In light of a global rise of patients with type 2 diabetes and obesity, non-alcoholic fatty liver disease (NAFLD), now known as metabolic dysfunction-associated fatty liver disease (MAFLD) or metabolic dysfunction-associated steatotic liver disease (MASLD), will become the leading causes of hepatocellular carcinoma (HCC), with the annual occurrence of MASLD-driven HCC expected to increase by 45-130% by 2030. Although MASLD has become a serious major public health threat globally, the exact molecular mechanisms mediating MASLD-driven HCC remain an open problem for future investigation. Meanwhile, emerging studies are focusing on the utility of bioactive compounds to halt the progression of MASLD to MASLD-driven HCC. In this review, we first briefly review the recent progress of the possible mechanisms of pathogenesis and progression for MASLD-driven HCC. We then discuss the application of bioactive compounds to mitigate MASLD-driven HCC through different modulatory mechanisms encompassing anti-inflammatory, lipid metabolic, and gut microbial pathways, providing valuable information for future treatment and prevention of MASLD-driven HCC. Nonetheless, clinical research exploring the effectiveness of herbal medicines in the treatment of MASLD-driven HCC is still warranted.